Occupational health needs of universities: a review with an emphasis on the United Kingdom. Issue 3 (23rd February 2006) - Venables, K M; Allender, S
Abstract : This study describes the needs of universities in relation to planning the provision of occupational health services, by detailing their occupational hazards and risks and other relevant factors. The paper presents the results of (1) an enquiry into publicly available data relevant to occupational health in the university sector in the United Kingdom, (2) a literature review on occupational health provision in universities, and (3) selected results from a survey of university occupational health services in the UK. Although the enquiry and survey, but not the literature review, were restricted to the UK, the authors consider that the results are relevant to other countries because of the broad similarities of the university sector between countries. These three approaches showed that the university sector is large, with a notably wide range of occupational hazards, and other significant factors which must be considered in planning occupational health provision for individual universities or for the sector as a whole.